Emergency Department Use and Barriers to Health Care Among Homeless and Uninsured Patients at a Student-Run Free Clinic - Shayan Bhathena; Leticia Moczygemba; Kenneth Lawson (Journal of Student-Run Clinics, 2020)
Background: Free clinics often provide healthcare to homeless individuals who face barriers to accessing primary care and other healthcare services. This study aimed to assess: (1) barriers to healthcare experienced by uninsured and homeless patients at a student-run free clinic; (2) patient perceptions of helpfulness of social service resources; and (3) relationships between barriers and emergency department (ED) use and health status.Methods: In 2017, patient interviews were conducted at a student-run free clinic in central Texas. A structured questionnaire was used to collect demographics, perceived health status, ED usage, and ratings of barriers to healthcare and helpfulness of social service resources. Data analysis included descriptive and bivariate analyses, used to examine the relationship between barriers to healthcare services and ED use, and between barriers to healthcare services and health status.Results: In total, 48 patients participated. The highest-rated barrier to receiving medical care was cost of healthcare, followed by lack of transportation and lack of insurance. Of the top 5 most utilized resources, Medicaid was rated as most helpful, followed by a medical assistance program and caseworkers. Reported ED use was significantly associated with higher ratings of lack of transportation as a barrier (p=0.03), use of a local mental health services program (p=0.01), and having insurance coverage through a local medical assistance program, Medicaid, or Medicare (p=0.01). No significant relationship was found between any healthcare barrier and health status.Conclusions: This study found that the highest barrier to medical care was cost of healthcare and that lack of transportation was significantly related to ED usage. In the future, this clinic might consider introducing a resource that addresses the barrier of transportation for its patients.